Proprioceptive-dependent Training for Enhancing Skill Performance: Changes in Perceived and Actual Performance according to Distance Increase during Golf Putt - Tae-Ho Kim; Duk-Chan Jang; Jun-Ho Ha (Korea Institute of Sport Science, 2021)
PURPOSE The purpose of this study was to investigate the applicability of proprioceptive-dependent training as an effective physical training method by analyzing the effects of proprioceptive-dependent training on the accuracy of perceived and actual distance as well as the correlation between the changes in the two variables. METHODS Thirty-six male college students took part in the experiment. Participants were beginners with no previous experience in golf or less than five times of experience. They were randomly assigned to one of three groups; proprioceptive-dependent training, visual-dependent training, and control, maintaining the same sample size per group. The experiment was carried out in the order of pre-test, practice section, and post-test. In the pre-test, putting was tested to assess the accuracy of perceptual and actual distance in the 1-15m distance in a random order using a digital putting analyzer. In the practice section, proprioceptive-dependent and visual-dependent training groups practiced a total of 90 putting, six times per distance with the eyes closed or open. The post-test was the same as the pre-test. The accuracy of perceived and actual distance and the correlation between the changes in the two variables were analyzed using the calculated absolute errors. RESULTS The results of this study showed that there was no difference between groups in pre-test. In contrast, in post-test, the absolute error was significantly decreased in the order of proprioceptive-dependent training, visual-dependent training, and control group in the three distance conditions. Besides, for the proprioceptive-dependent training group and visual-dependent training group, there was a significant positive correlation between the changes in the accuracy of perceived and actual distance. CONCLUSIONS These results provide insight into the applicability of proprioceptive-dependent training for enhancing motor performance by showing the effects of proprioceptive-dependent training on perceived distance, actual distance, and the correlation between the two variables.